The Relationship Between Smoker Identity and Smoking Cessation Among Young Smokers: The Role of Smoking Rationalization Beliefs and Cultural Value of Guanxi - Chen, Haide; Fan, Yumeng; Li, Xinwei; Gao, Lingfeng; Li, Weijian (Frontiers in Psychiatry, 2022)
Although the relationship between smoker identity and smoking cessation behavior has been confirmed, the role of smoking-related beliefs and cultural values in this relationship for young smokers is little known. The present study aimed to examine whether the relationship between smoker identity and smoking cessation behavior would be mediated by smoking rationalization beliefs and/or intention to quit smoking and whether the effect of smoker identity on smoking cessation behavior was moderated by cultural value of guanxi. A total of 708 young smokers participated in the study and completed questionnaires that measured smoker identity, smoking rationalization beliefs, intention to quit smoking, smoking cessation behavior and cultural value of guanxi. The results showed: (1) the relationship between smoker identity and smoking cessation behavior was negative and significant. (2) the mediating effect of intention to quit smoking and the serial mediating effect of “smoking rationalization beliefs → intention to quit smoking” on the relationship between smoker identity and smoking cessation behavior was significant. (3) both the serial mediating effect of “smoking rationalization beliefs → intention to quit smoking” and the direct effect of smoker identity on smoking cessation behavior were moderated by cultural value of guanxi. The current findings increased understanding of psychosocial mechanisms underlying the hindering effect of smoker identity on smoking cessation and suggested the role of smoking rationalization beliefs and cultural value of guanxi should be considered in smoking cessation interventions for young smokers.